Maternal syphilis in the Federal District, Brazil: a five-year analysis of notified data (2019–2023) - Santiago, Paula Beatriz de Medeiros; Meneses, Maria Eduarda Santiago; Pereira, Luiza de Lima; Meneses, Maria Fernanda Santiago; da Silva, Pamela Araújo; Mariz, Fabiana Nunes de Carvalho; Gomes, Ciro Martins; de Araújo, Carla Nunes (Frontiers in Epidemiology, 2025)
Syphilis, caused by the bacterium Treponema pallidum, is among the most prevalent STIs globally and represents a significant public health challenge in Brazil. Vertical transmission can occur at any stage of pregnancy, leading to severe consequences such as miscarriage, stillbirth, preterm birth, and low birth weight. In severe cases, congenital syphilis may result, potentially causing deformities, neurological damage, or even neonatal death. Maternal syphilis (MS) occurrence is often influenced by social inequalities, meager income, and educational levels, which present further public health challenges. We evaluated the incidence of maternal syphilis in the Administrative Regions of the Federal District (FD), Brazil, from 2019 to 2023, highlighting the distribution of notified cases regarding the sociodemographic profile of affected pregnant women. We utilized data from the Info Saúde DF portal (https://info.saude.df.gov.br/sifilissalasit/) and the latest report from the most recent District Household Sample Survey. The cumulative incidence of MS was 25.3 cases per 1,000 live births. Simple linear regression analysis was used to assess the association between MS incidence and sociodemographic characteristics. A moderate negative correlation was observed (r = −0.4038), indicating that higher education levels are associated with a lower incidence of MS. Lower-income populations living in the FD, Brazil, face a heightened risk of maternal syphilis, possibly due to a combination of economic and social factors, suggesting that public health policies aimed at controlling the disease should prioritize this population.